2018
DOI: 10.1186/s12904-018-0310-8
|View full text |Cite
|
Sign up to set email alerts
|

Health service utilisation during the last year of life: a prospective, longitudinal study of the pathways of patients with chronic kidney disease stages 3-5

Abstract: BackgroundChronic kidney disease (CKD) is a growing global problem affecting around 10% of many countries’ populations. Providing appropriate palliative care services (PCS) to those with advanced kidney disease is becoming paramount. Palliative/supportive care alongside usual CKD clinical treatment is gaining acceptance in nephrology services although the collaboration with and use of PCS is not consistent.MethodsThe goal of this study was to track and quantify the health service utilisation of people with CKD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
4
0
2
Order By: Relevance
“…(28) Una investigación realizada por Aoife C. Lowney et.al (30) , a través de la aplicación de la escala HRQoL (Health-related quality of life) a diversos pacientes (todos mayores de 18 años), postula que existe una disminución de la calidad de vida asociada a la ERCA en pacientes sometidos a diálisis. (31) Otro punto para considerar es la necesidad de recibir atención de salud durante el transcurso de la ERCA. Esto se aborda en el estudio realizado por Chambers S et al (30) donde se cuantificó la utilización de servicios de salud, incluyendo la asistencia a unidad de emergencia y requerimiento de hospitalización, tanto en pacientes en diálisis como en manejo conservador y se estableció que aquellos en diálisis presentaban más hospitalizaciones y visitas al servicio de urgencias que aquellos con manejo conservador.…”
Section: Resultsunclassified
“…(28) Una investigación realizada por Aoife C. Lowney et.al (30) , a través de la aplicación de la escala HRQoL (Health-related quality of life) a diversos pacientes (todos mayores de 18 años), postula que existe una disminución de la calidad de vida asociada a la ERCA en pacientes sometidos a diálisis. (31) Otro punto para considerar es la necesidad de recibir atención de salud durante el transcurso de la ERCA. Esto se aborda en el estudio realizado por Chambers S et al (30) donde se cuantificó la utilización de servicios de salud, incluyendo la asistencia a unidad de emergencia y requerimiento de hospitalización, tanto en pacientes en diálisis como en manejo conservador y se estableció que aquellos en diálisis presentaban más hospitalizaciones y visitas al servicio de urgencias que aquellos con manejo conservador.…”
Section: Resultsunclassified
“…This has been highlighted independent of the responsible disease, whether it is cancer or organ failure, with a growing resort to emergency and hospital services during their last year of life. 42 45 Moreover, it has been shown that home palliative care allows reducing the feeling of burden related to the symptoms. 41…”
Section: Discussionmentioning
confidence: 99%
“…This has been highlighted independent of the responsible disease, whether it is cancer or organ failure, with a growing resort to emergency and hospital services during their last year of life. [42][43][44][45] Moreover, it has been shown that home palliative care allows reducing the feeling of burden related to the symptoms. 41 Among patients receiving early palliative care, this followup would allow to rapidly detect the onset of complications that could be specifically treated, with an impact as much on quality of life as on survival.…”
Section: An Increasingly Early Palliative Care Requiring An Evolution...mentioning
confidence: 99%
“…The majority (79%) visited the emergency department, multiple visits were common, and 84% required in-patient admission. 23 There are limited data on the cost effectiveness of RSC frameworks 22 ; however, there is a well-established cost benefit in oncology. 24 RSC/PC may decrease hospitalizations, intensive care, and emergency department admissions.…”
Section: Sa: the Current Situationmentioning
confidence: 99%
“…The aim is to reduce the deaths in acute care facilities through better symptom management and planned care pathways. 23 Further research evaluating cost and health outcomes in ESKD is required.…”
Section: Sa: the Current Situationmentioning
confidence: 99%